Efeito da incorporação de quitosana e quitosana modificada na qualidade, funcionalidade tecnológica e vida de prateleira de salsichas com reduzido teor de gordura - Amaral, Deborah Silva do (2016)
The aim of this study was to evaluate the inclusion of chitosan and modified chitosan (chitosan-glucose) in appropriate concentration to meet the health claim in sausages with reduced fat, on the technological functionality and shelf life of these sausages. For this, an initial study was conducted, in which chitosan (2% w/w) was added to sausages prepared with pork and three levels of fat (5%, 12.5% and 20% w/w). The sausages were submitted to cold storage at 4 ± 1 °C for 15 days and evaluated in terms of microbiological, physic-chemical and sensory parameters. Subsequently, considering the absence of studies on incorporation of chitosan in meat goat products, carried out a second study, similar to the above to evaluate the effect of incorporation of chitosan (2% w/w) in sausage made with goat meat, and similar levels of fat in the microbiological and physico-chemical quality during cold storage (4 ± 1 °C) for 15 days. Finally, in the third study was evaluated the effect of the derivative of chitosan (2% w/w) in comparison with chitosan base (2% w/w) in sausage made with goat meat and reduced fat content (10% w/w). The sausages were stored at 4 ± 1 ° C for 21 days and evaluated by microbiological, physic-chemical and sensory parameters. In all three studies a formulation without the addition of polymers (chitosan and modified chitosan) was used as control. The results indicated that the use of 2% (w / w) chitosan and its derivative (corresponding to 1 g of chitosan per sausage of 50g each in a portion of 150g) to ensure ingestion of 3 g of chitosan per day is technologically feasible for use in the preparation of sausage with pork and goat meat. In addition to the functional potential, chitosan and chitosan derivative provided increased stability of the treated sausages since it caused the reduction of microbial growth when compared to the control sample. Additionally, they provided an improvement in red color, resulting in positive effects on the appearance, a more stable emulsion for the greater ability to bind water and fat, and a firmer texture to increase the compression forces, without negatively affecting the sensory properties of sausages. The chitosan and modified chitosan showed similar behavior, but the use of chitosan resulted in higher antioxidant activity than its derivative, considering further reduction of TBARS values and increased content of unsaturated fatty acids and poly-unsaturated. However, the chitosan derivative promoted a greater red color (a *) and lower hardness than chitosan. Therefore, the results of the use of chitosan in the manufacture of goat sausages, which was studied for the first time, indicated that the chitosan and modified chitosan showed potential interest to be used in the preparation of meat products, since they can provide higher quality and shelf life, adding value to the raw material of low commercial value, besides allow to obtain of a functional product with the health claim and fat reduction.